The Relationship of Organizational Factors to Compliance with the Filling out of Medical Resumes by the Doctor in Charge of Patients at Panti Wilasa Citarum Hospital Semarang - Inneke Elysia Lavender; Chriswardhani Suryawati; Cahya Tri Purnami (International Journal Labs, 2025)
This study aims to analyze the relationship between organizational factors, including communication, leadership, compensation, supervision, and resources, and DPJP compliance in filling out medical resumes in accordance with BPJS Kesehatan regulations. This study uses a quantitative descriptive design with a cross-sectional time approach. The results of observations showed that the average DPJP compliance score at Panti Wilasa Citarum Hospital Semarang in filling out the medical resume was 5.29 (score 0–8). Organizational factors included leadership factors with an average score of 59.04 (score 11–77), compensation factors with an average score of 29.94 (score 10–70), communication factors with an average score of 31.72 (score 6–42), supervision factors with an average score of 47.88 (score 10–70), and resource factors with an average score of 54.42 (score 10–70). Communication factors showed a significant association with compliance (r = 0.39; p = 0.006), while leadership factors (r = 0.17; p = 0.25), compensation (r = 0.06; p = 0.68), supervision (r = 0.13; p = 0.36), and resources (r = 0.25; p = 0.08) showed no meaningful relationship. Multivariately, organizational factors have no relationship with DPJP compliance in filling out medical resumes in accordance with BPJS Kesehatan regulations. Communication has a meaningful relationship with DPJP compliance in filling out medical resumes in accordance with BPJS Kesehatan regulations. Meanwhile, the factors of leadership, compensation, supervision, and resources are not meaningfully related.